Potential Study of Applying Traffic Congestion Index to Simulate Property Price Changes - Azhar, Azmi; Sangeetha, Arjinan; Chan, Siew Chong (INTI International University, 2022)
Urban congestion issue is considered as part of major issues that affects the urban development progress and also the living qualities. One of the impacts is reducing the properties prices due to demolishing in property values. This paper provides an insight onto the possibility to simulate the changes of property prices due to variation in different traffic congestion conditions. Firstly, a number of discussions are conducted onto lack of proper analysis tool in assessing the relationship between the extent of urban traffic congestion condition and the fluctuations of property prices in urban areas. Secondly, the aim of this paper is to simulate and generate a modelling framework in order to fill up the niche areas in order to justify the validation of this tool in analyzing the implication of urban traffic congestions onto the changes of property prices. In order to ensure the research work can be implemented, thus a combination of traffic congestion data and property price data which are further integrated using Overlay Mapping Method by referring to i-PLAN, and outcomes are further evaluated through correlation analysis and hypothesis testing. Based on these research inputs, it is thus estimated that generated outputs in index format is able to provide an important guideline for the further developer in making their decisions to acquire property for development.